One same deontology for different sciences? Review of national and international guidelines in ethics of scientific research - Winkler Müler, María Inés; Letelier Soto, Antonio (Acta Bioethica, 2014)
A review of legal Chilean norms and international ethical codes about research involving human beings was carried out, through a mix methodology of content analysis, with the purpose of identifying the presence of words associated to psychology, as an intermediate science between biomedicine and social sciences. Finding ethical issues present in both types of norms was looked out to delimit the differences between those associated to biomedical sciences and those to psychology. Results show a scarce presence of norms linked to the particularities of psychology and a limited and poor use of concepts, demonstrating that bioethics, mainly based on biomedical developments, does not respond adequately to the needs for conflict resolution in the research context of psychology.